2004
DOI: 10.1213/01.ane.0000133913.07342.b9
|View full text |Cite
|
Sign up to set email alerts
|

S(+)-Ketamine as an Analgesic Adjunct Reduces Opioid Consumption After Cardiac Surgery

Abstract: There are no studies evaluating S(+)-ketamine for pain management after sternotomy. In this prospective, randomized, double-blind, placebo-controlled clinical trial, we evaluated the efficacy and feasibility of S(+)-ketamine as an adjunctive analgesic after cardiac surgery. Ninety patients scheduled for elective coronary artery bypass grafting (CABG) were randomized to receive either a 75 microg/kg bolus of S(+)-ketamine followed by a continuous infusion of 1.25 microg . kg(-1) . min(-1) for 48 h (n = 44) or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 29 publications
3
53
1
3
Order By: Relevance
“…[11,12] Lahtinen et al have documented that a continuous intravenous infusion of ketamine 1.25 µg/kg/min potentiates opioid patient controlled analgesia following cardiac surgery. [14] Based on the dose regimens in these studies, we assessed the effect of intravenous low-dose ketamine 0.05 mg/kg/h on continuous intercostal nerves block following thoracotomy. Our data indicated that low-dose intravenous ketamine did not decrease pain scores and rescue morphine requirement in patients having continuous intercostal analgesia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] Lahtinen et al have documented that a continuous intravenous infusion of ketamine 1.25 µg/kg/min potentiates opioid patient controlled analgesia following cardiac surgery. [14] Based on the dose regimens in these studies, we assessed the effect of intravenous low-dose ketamine 0.05 mg/kg/h on continuous intercostal nerves block following thoracotomy. Our data indicated that low-dose intravenous ketamine did not decrease pain scores and rescue morphine requirement in patients having continuous intercostal analgesia.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports did not find an increased sedation in patients receiving intravenous low-dose ketamine following surgery. [12,14,16,17] Only Ilkjaer et al reported a significantly higher level of sedation in patients given intravenous ketamine in combination with epidural bupivacaine after renal surgery. [15] Ketamine psychomimetic side effects include blurred vision, vertigo, hallucination, and nightmares.…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated an evident preemptive effect with epidural analgesia, reducing pain intensity and consumption of complementary analgesics, thus increasing the time to request the first complementation 19 . Other authors also obtained reduction of intensity of postoperative pain by administering ketamine before and during surgery 20,21 . Nevertheless, they did not obtain an improved analgesic effect with ketamine when administered before incision or after surgery 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine is an antagonist of NMDA receptors and the S(+)-ketamine isomer is more powerful than the racemic drug and causes less adverse effects [5][6][7][8][9][10] . Although many studies have used ketamine, its preemptive effect is controversial [11][12][13] . There is not much information available about administration of epidural ketamine and attenuation of inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Hier sind aber nicht die μ-Rezeptoren betroff en, womit es nicht zu einer Atemdepression kommt. Vor allem in niedriger Dosierung zeigt S-Ketamin einen opioidsparenden Eff ekt [36,37]. Zusätzlich kann eine mög-liche opioid-induzierte Hyperalgesie durch Einsatz von Ketamin reduziert werden [38].…”
Section: Ketaminunclassified